PS02 "We Can all just Get on a bus and Go": Rethinking Independent Mobility in the Context of the Universal Provision of Free Bus Travel to Young Londoners. (17th September 2012) - Goodman, A; Jones, A; Roberts, H; Steinbach, R; Green, J
Abstract : Background: Recent years have seen increasing attention to 'independent mobility' as a determinant of children's physical health and psychosocial development. Previous research, however, largely frames independent mobility as a matter of having parental permission to travel without adults. It also predominantly focuses upon walking any cycling trips in the local area by young children. We therefore aimed to extend the independent mobility literature by examining mobility on public transport, mobility beyond the local area and mobility by adolescents. For this we use as a case study the recent provision of universal free bus travel to all young people in London, UK. We argue that idea of independent mobility can usefully be situated within the broader conception of opportunity and process freedoms which underpin Amartya Sen's influential 'capabilities approach' to human development. Methods: As part of the On the buses study, 118 young Londoners (age 12–18, 65 females) took part in 43 in-depth interviews (group size 1–3, 61 individuals) and 10 focus groups (group size 4–8, 57 individuals). Interviews and focus groups elucidated tacit, or everyday, influences on and effects of young people's transport mode choices. We analysed this data qualitatively, drawing on techniques from the constant comparative method, including initial micro-level open coding and an iterative approach to identifying and refining emerging conceptual categories. Results: Free bus travel enhanced young Londoners' capability to shape their daily mobility, both directly by increasing financial access and indirectly by facilitating the acquisition of the necessary skills, travelling companions and confidence. These capabilities in turn extended both opportunity freedoms (e.g. facilitating non-"necessary" recreational and social trips) and process freedoms (e.g. feeling more independent by decreasing reliance on parents). Moreover, the universal nature of the entitlement often seemed crucial as it meant that free bus travel was typically held by all of a peer group. This rendered buses a socially inclusive way for groups to travel and spend time together, thereby enhancing group-level capabilities. Conclusion: We believe this attention to individual and group-level capabilities for self-determination provides the basis for a broader and more child-centered view of independent mobility than is typical in health research. The importance of the universal nature of the entitlement to free bus travel also provides an example of how policy interventions with universal coverage may have effects which are more than the 'sum of the parts' of alternative, targeted approaches.